2014
DOI: 10.1038/eye.2013.304
|View full text |Cite|
|
Sign up to set email alerts
|

Bimatoprost 0.01% vs bimatoprost 0.03%: a 12-month prospective trial of clinical and in vivo confocal microscopy in glaucoma patients

Abstract: Results Global clinical score (the sum of pruritus, stinging/burning, blurred vision, sticky eye sensation, eye dryness sensation, and foreign body sensation) significantly decreased in the bimatoprost 0.01% group from baseline 4.7±3.8 to 2.9±2.3 (Po0.001) and 2.5±2.0 (Po0.001) at 6-month and 12-month follow-ups, respectively. Comparison between groups showed differences at both follow-up visits (P ¼ 0.003 and Po0.001, respectively). In vivo confocal microscopy revealed a significant increase in goblet cell de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 44 publications
(47 reference statements)
0
31
0
Order By: Relevance
“…Additionally, while BAK is known to be associated with ocular side effects such as conjunctival hyperemia, several studies have shown milder and/or fewer reports of conjunctival hyperemia after treatment with bimatoprost 0.01% in BAK 200 ppm, compared with bimatoprost 0.03% in BAK 50 ppm. 21 , 24 , 30 , 31 These findings suggest that a higher BAK concentration does not necessarily lead to a higher rate of conjunctival hyperemia.…”
Section: Clinical Correlation With Evidence For Use Of Bimatoprost Twmentioning
confidence: 85%
See 1 more Smart Citation
“…Additionally, while BAK is known to be associated with ocular side effects such as conjunctival hyperemia, several studies have shown milder and/or fewer reports of conjunctival hyperemia after treatment with bimatoprost 0.01% in BAK 200 ppm, compared with bimatoprost 0.03% in BAK 50 ppm. 21 , 24 , 30 , 31 These findings suggest that a higher BAK concentration does not necessarily lead to a higher rate of conjunctival hyperemia.…”
Section: Clinical Correlation With Evidence For Use Of Bimatoprost Twmentioning
confidence: 85%
“…15 In two identically designed, Phase III pivotal studies supporting the efficacy and safety of bimatoprost 0.03% ophthalmic solution (preserved with 50 ppm benzalkonium chloride [BAK]), once-daily dosing was found to be optimal for a monotherapy formulation, with twice-daily dosing offering no efficacy advantage. 16 20 The currently available bimatoprost 0.01% formulation (containing 200 ppm BAK) has been found to be as effective as the 0.03% formulation when administered once daily, 21 24 most likely because higher BAK concentrations were shown to enhance corneal penetration of bimatoprost. 25…”
Section: Introductionmentioning
confidence: 99%
“… 14 Bimatoprost 0.01% has demonstrated equivalent IOP-lowering efficacy and improved tolerability compared with bimatoprost 0.03%, including less frequent and severe conjunctival hyperemia. 8 , 12 The study by Katz et al confirmed that bimatoprost 0.01% is effective and equivalent to bimatoprost 0.03% in lowering IOP over a 12-month treatment period. 8 …”
Section: Discussionmentioning
confidence: 97%
“…The efficacy observed in the topical treatment arm was consistent with the 30%-35% IOP lowering typically reported in studies of topical bimatoprost 0.03%. 21 A bimatoprost 0.01% formulation that demonstrates the same efficacy and improved tolerability 22,23 is now the only topical ophthalmic formulation of bimatoprost available for use in the United States.…”
Section: This Is the First Report Of The Iop-lowering Efficacymentioning
confidence: 99%